Lack of viral control and development of combination antiretroviral therapy escape mutations in macaques after bone marrow transplantation. (24th August 2015) - Peterson, Christopher W.; Haworth, Kevin G.; Polacino, Patricia; Huang, Meei-Li; Sykes, Craig; Obenza, Willimark M.; Repetto, Andrea C.; Kashuba, Angela; Bumgarner, Roger; DeRosa, Stephen C.; Woolfrey, Ann E.; Jerome, Keith R.; et al.
Abstract : Objective: We have previously demonstrated robust control of simian/human immunodeficiency virus (SHIV1157-ipd3N4) viremia following administration of combination antiretroviral therapy (cART) in pigtailed macaques. Here, we sought to determine the safety of hematopoietic stem cell transplantation (HSCT) in cART-suppressed and unsuppressed animals. Design: We compared disease progression in animals challenged with SHIV 100 days post-transplant, to controls that underwent transplant following SHIV challenge and stable cART-dependent viral suppression. Methods: SHIV viral load, cART levels, and anti-SHIV antibodies were measured longitudinally from plasma/serum from each animal. Flow cytometry was used to assess T-cell subset frequencies in peripheral blood and the gastrointestinal tract. Deep sequencing was used to identify cART resistance mutations. Results: In control animals, virus challenge induced transient peak viremia, viral set point, and durable suppression by cART. Subsequent HSCT was not associated with adverse events in these animals. Post-transplant animals were challenged during acute recovery following HSCT, and displayed sustained peak viremia and cART resistance. Although post-transplant animals had comparable plasma levels of antiretroviral drugs and showed no evidence of enhanced infection of myeloid subsets in the periphery, they exhibited a drastic reduction in virus-specific antibody production and decreased T-cell counts. Conclusions: These results suggest that virus challenge prior to complete transplant recovery impairs viral control and may promote drug resistance. These findings may also have implications for scheduled treatment interruption studies in patients on cART during post-HSCT recovery: premature scheduled treatment interruption could similarly result in lack of viral control and cART resistance. Abstract : Supplemental Digital Content is available in the text